INTEGRATION OF ECONOMIC LAW AND HEALTH LAW IN MINOR THEFT HANDLING POLICIES: LITERATURE ANALYSIS - Gunawan Widjaja (RADJA PUBLIKA, 2025)
This study aims to analyse the integration of economic law and health law in policies addressing petty theft through a literature review. Petty theft is often triggered by economic factors such as poverty and unemployment, as well as health factors such as mental disorders, which are not fully accommodated in the conventional criminal justice system. Literature analysis shows that policies for handling petty theft that are solely oriented towards punishment tend to be ineffective and have the potential to cause social injustice. The integration of the two fields of law through a restorative justice approach and cross-sector collaboration can provide a more comprehensive, fair, and humane solution. Synergy between law enforcement agencies, social institutions, and health services is needed, as well as regulatory reforms, so that policies for handling petty theft can be more responsive to the economic and health conditions of the perpetrators.